1984
DOI: 10.1159/000275693
|View full text |Cite
|
Sign up to set email alerts
|

Benign Paroxysmal Vertigo in Childhood: A Migraine Equivalent

Abstract: The two main problems in defining and classifying the syndrome of benign paroxysmal vertigo (BPV) in childhood are the vestibular function pattern and the relationship between BPV and migraine. 13 children suffering from this syndrome were submitted to complete otoneurological examination, including caloric and rotational labyrinthine stimulation with ENG recording, and to headache provocation tests with nitroglycerin, histamine and fenfluramine. Vestibular responses were normal in all except 2 cases which pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Many children with initial vertigo and suspected BPVC go on to develop migraine (20,22,23,(31)(32)(33)(34). Child migraine is different from adult 'classical' migraine (19) in that the most intense symptom (and common complaint) is usually gastrointestinal upset and fever rather than headache or visual disturbances (31).…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Many children with initial vertigo and suspected BPVC go on to develop migraine (20,22,23,(31)(32)(33)(34). Child migraine is different from adult 'classical' migraine (19) in that the most intense symptom (and common complaint) is usually gastrointestinal upset and fever rather than headache or visual disturbances (31).…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Child migraine is different from adult 'classical' migraine (19) in that the most intense symptom (and common complaint) is usually gastrointestinal upset and fever rather than headache or visual disturbances (31). Also, children's migraine attacks are often more frequent, of shorter duration (lasting less than 2 h) (35), may not be experienced as throbbing (35), and may present with a less clearly defined pattern of prodromal expression.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…BPV is probably a common but misunderstood and unrecognized condition in small children. 1,2,[4][5][6][7][8][9][10][11] In our experience, awareness of the condition has increased our detection rate of BPV during the past 6 years. The diagnostic criteria have been purely clinical, and BPV has commonly been a diagnosis of exclusion.…”
Section: Discussionmentioning
confidence: 76%
“…2 However, caloric tests have in general been normal. [7][8][9] The mechanism for increased CK-MB in BPV remains unknown. We have shown that cTnI levels are normal in BPV, thus excluding a cardiac origin of the CK-MB increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation